2022
DOI: 10.1093/forestry/cpac030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low phosphorus availability on root cambial activity, biomass production and root morphological pattern in two clones of Chinese fir

Abstract: Phosphorous (P) is a crucial limiting nutrient for plant growth and development in terrestrial ecosystems. As one of the most important subtropical coniferous tree species, Chinese fir (Cunninghamia lanceolata) plays a major role in timber supply, climate mitigation and forest recreation. In this study, two Chinese fir clones (020 and 061) with a high growth rate were subjected to two levels of P supply in a greenhouse pot experiment: P-deficient P0 (no P supply) and P-replete P1 (1.0 mmol L−1 KH2PO4). Our obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This approach represents a competent model for studying cambial activity and wood formation. This review also showed that temperature, water, and phosphorus dynamics indicate past and current functions of different tree species [113]. In particular, this review demonstrates the need to research mechanisms within a classified scheme and how identified stresses vary in relation to the physiological and morphological features of different tree species over specific periods.…”
Section: Discussionmentioning
confidence: 90%
“…This approach represents a competent model for studying cambial activity and wood formation. This review also showed that temperature, water, and phosphorus dynamics indicate past and current functions of different tree species [113]. In particular, this review demonstrates the need to research mechanisms within a classified scheme and how identified stresses vary in relation to the physiological and morphological features of different tree species over specific periods.…”
Section: Discussionmentioning
confidence: 90%
“…Specific root length, specific root area, and specific root tip density of Chinese fir fine roots in mature forests show a decreasing trend with increasing forest age, and the nutrient foraging ability decreases; however, physiological compensation occurs by increasing the nitrogen concentration of the fine roots [18]. By observing the cross-sectional microstructure of the fine roots of Chinese fir, it was found that the activity of the cambium was significantly increased in an environment with sufficient phosphorus, which promoted an increase in root diameter and biomass and improved the quality of seedlings [19]. With increasing research on the relationship between global environmental change and root systems, fine roots are an important bridge connecting the external morphology, internal physiological activity, and functions of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the relationship between the N:P ratio in green foliage and soil nutrient availability, highlighting the internal linkages between nutrient demand and supply [1,5,6,[9][10][11][12]. In response to low soil P availability, plants typically reduce foliage P concentration [13][14][15]. The biological characteristics of plant species contribute to the variations in nutrient requirements throughout different growth stages [16].…”
Section: Introductionmentioning
confidence: 99%